2007
DOI: 10.1016/j.mad.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A common variant of the p16INK4a genetic region is associated with physical function in older people

Abstract: Abstractp16 INK4a is active in cell senescence, ageing and tumor suppression. Deletion of the small p16 INK4a / ARF / p15 INK4b region occurs in many cancers. We screened 25 common polymorphisms across the region and 3 related genes for associations with physical functioning in older people.In an initial sample of 938 (aged 65 to 80yrs) from the EPIC study (Norfolk, UK) the rs2811712 SNP minor allele (located between the shared p16 INK4a / ARF locus and p15 INK4b ) was associated with reduced physical impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…Polymorphisms are associated with aging (Saxena et al, 2007;Scott et al, 2007;Zeggini et al, 2007;Melzer et al, 2007;) P16-deletion: improved regenerative capacity in different stem cell compartments: HSCs, neuronal stem cells, pancreatic islets. (Molofsky et al, 2006;Krishnamurthy et al, 2006;Janzen et al, 2006;Stepanova and Sorrentino, 2005) No improvement in organ maintenance and lifespan in p16Ink4A, P19ARF compound mutant mice (Khoo et al, 2007) (Lynch and Lynch, 2005); Mismatch repair defect Colorectal cancer, extra-CRC cancers.…”
Section: Cell Intrinsicmentioning
confidence: 99%
“…Polymorphisms are associated with aging (Saxena et al, 2007;Scott et al, 2007;Zeggini et al, 2007;Melzer et al, 2007;) P16-deletion: improved regenerative capacity in different stem cell compartments: HSCs, neuronal stem cells, pancreatic islets. (Molofsky et al, 2006;Krishnamurthy et al, 2006;Janzen et al, 2006;Stepanova and Sorrentino, 2005) No improvement in organ maintenance and lifespan in p16Ink4A, P19ARF compound mutant mice (Khoo et al, 2007) (Lynch and Lynch, 2005); Mismatch repair defect Colorectal cancer, extra-CRC cancers.…”
Section: Cell Intrinsicmentioning
confidence: 99%
“…[9][10][11] A genome-wide association study has shown association of the CDKN2A locus with an increased risk of the age-related frailty syndrome. 12 In addition, increased p16 INK4a expression causes the age-dependent decline in proliferation of self-renewing cellular compartments such as HSCs, 13 which give rise to immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…9-11 A genome-wide association study has shown association of the CDKN2A locus with an increased risk of the age-related frailty syndrome. 12 In addition, increased p16 INK4a expression causes the age-dependent decline in proliferation of self-renewing cellular compartments such as HSCs, 13 which give rise to immune cells.Although the role of p16 INK4a in mature immune cells has not yet been investigated, several studies has shown that the CDKN2A locus is associated with an increased risk for coronary heart disease, 14 atherosclerosis, 15 and type 2 diabetes (T2D). 16 In these pathologies, immune cells, such as macrophages, play a crucial role.…”
mentioning
confidence: 99%
“…p16 INK4a and ARF may also be broadly important to diseases of aging beyond their function in stem cells. Specifically, three research consortia that undertook genome-wide association studies across large, carefully annotated patient samples have reported an association between single nucleotide polymorphisms (SNPs) near to INK4a/ARF locus and frailty (Melzer et al, 2007), atherosclerotic heart disease (ASHD) (Helgadottir et al, 2007) (McPherson et al, 2007, and type-2 diabetes (Saxena et al, 2007;Zeggini et al, 2008) in large human cohorts. However, few of the associated SNPs near the locus, and associated with these phenotypes, are not in linkage disequilibrium with each other, which suggests that more than one polymorphism near the locus influences these aging phenotypes.…”
Section: Wwwintechopencommentioning
confidence: 99%